Endoscopic submucosal dissection of gastric lesions using the “yo-yo technique” - Baldaque-Silva, F.; Vilas-Boas, F.; Velosa, M.; Macedo, G. (Endoscopy, 2013)
One of the main difficulties during endoscopic submucosal dissection (ESD) is the mobilization of the partially resected lesion in order to improve access to the lesion edges and the dissection plane. In the current study, the feasibility and safety of a new “yo-yo technique” to facilitate ESD procedures were evaluated. A total of 17 consecutive patients with gastric lesions were included. A standard hemoclip and snare were used to pull and push the lesion margins in order to increase the access to the lesion edges and to the submucosal space. All lesions were resected en bloc, without perforation or significant bleeding requiring blood transfusion, and all patients were discharged within 7 days. Resected specimens and lesions were 24 – 58 mm (mean 36 mm) and 18 – 45 mm (mean 25 mm) in size, respectively. The “yo-yo technique” is feasible, easy, and safe, and allows the lesion to be pulled and pushed during the ESD procedure. Further use of this technique may lead to the expansion of its indications to other gastrointestinal regions.